13C urea breath test (UBT) in the diagnosis of Helicobacter pylori: why does it work better with acid test meals?. Issue 7 (1st July 2003) - Pantoflickova, D; Scott, D R; Sachs, G; Dorta, G; Blum, A L
Abstract : Background: Acid test meals may improve the accuracy of the 13 C urea breath test (UBT). This has been attributed to changes in gastric emptying rather than to the effects of gastric pH on Helicobacter pylori urease. Aims: To determine whether enhancement of 13 CO2 excretion in the UBT in H pylori infected volunteers by acidification of a test meal is due to a delay in gastric emptying. Methods: Urease activity in vitro was measured in intact bacteria and in bacterial homogenates. Urease activity in vivo was assessed by means of the UBT. Eleven H pylori infected subjects underwent UBTs with neutral Ensure (pH 7.0), acidified Ensure (pH 3.0), and apple juice (pH 3.0). Gastric emptying was assessed by 13 C sodium acetate breath test. Results: From pH 7 to pH 3, the in vitro urease activity of intact bacteria increased sixfold. In contrast, urease activity of bacterial homogenates was inactivated by low pH. In vivo, urease activity, as measured by the UBT 20 minutes after meal ingestion, was higher with apple juice (δ 13 CO2 =21.1; p=0.03) and acidified Ensure (δ 13 CO2 =25.5; p=0.01) than with neutral Ensure (δ 13 CO2 =12.5). Gastric emptying was faster with apple juice (Tmax =36.7 (8) minutes) but not with acidified Ensure (Tmax =63.3 (5) minutes; p=0.06) than with neutral Ensure (Tmax =65.0 (3) minutes; p=0.04). Conclusions: The higher UBT found with acidified compared with neutral test meals was independent of the emptying rates of the test meals but may have been due to medium acidity dependent activation of intra-bacterial urease in intact H pylori .